Various aspects of math can provide hours of fun, and amusement. One of these entails transpositions. Some basics on transpositions (and even and odd permutations) first:
A transposition is a permutation which interchanges two numbers and leaves the others fixed. The inverse of a transposition T is equal to the transposition T itself, so that:
T2 = I (identity permutation, e.g the permutation such that I(i) = i for all i = 1,...n)
A permutation p of the integers {1, . . . n} is denoted by
[1 .. . .. n]
[p(1).. p(n)]
So that, for example:
[1 2 3]
[2 1 3]
denotes the permutation p such that p(1) = 2, p(2) = 1, and p(3) = 3.
Now, let's look at EVEN and ODD permutations:
Let P_n denote the polynomial of n variables x1, x2……xn which is the product of all the factors x_i … xj with i < j. That is,
P_n(x1, x2... . xn) = P(x_i .. x_j)
The symmetric group S(n) acts on the polynomial P_n by permuting the variables. For p C S(n) we have:
P_n( x_p(1), x_p(2). . .x_p(n)) = (sgn p) P_n (x_1, x_2…..x_n)
where sgn p = +/-1. If the sign is positive then p is called an even permutation, if the sign is negative then p is called an odd permutation. Thus: the product of two even or two odd permutations is even. The product of an even and an odd permutation is odd.
Back to transpositions!
We just saw:
[1 2 3]
[2 1 3]
The above permutation is actually a transposition 2 <-> 1 (leaving 3 fixed).
Now, let p' be the permutation:
[1 2 3]
[3 1 2]
Then pp' is the permutation such that:
pp'(1) = p(p'(1)) = p(3) = 3
pp'(2) = p(p'(2)) = p(1) = 2
pp'(3) = p(p'(3)) = p(2) = 1
It isn’t difficult to ascertain that: sgn (ps) = (sgn p) (sgn s)
so that we may write:
pp' =
[1 2 3]
[3 2 1]
Now, find the inverse p^-1 of the above. (Note: the inverse permutation, denoted by p^-1 is defined as the map: p^-1 : Zn -> Zn),
Since p'(1) = 3, then p ^-1(3) = 1
Since p'(2) = 1 then p^ -1(1) = 2
Since p'(3) = 2 then p^ -1(2) = 3
Therefore:
p^-1 =
[1 2 3]
[ 2 3 1]
Problem: Express
p =
[1 2 3 4]
[2 3 1 4]
as the product of transpositions, and determine the sign (+1 or -1) of the resulting end permutation.
Let T1 be the transposition 2 <-> 1 leaving 3, 4 fixed, so:
T1 p =
[1 2 3 4]
[1 3 2 4]
Let T2 be the transposition 2 <-> 3 leaving 1, 4 fixed, so:
T2 T1 p =
[1 2 3 4]
[1 2 3 4]
Then:
T2 T1 p = I (identity)
TWO transpositions (T1, T2) operated on p, so that the sign of the resulting permutation (to reach identity) is +1
The permutation is even.
No comments:
Post a Comment